A three-ligand bimetallic complex catalyst and preparation method thereof
By developing a three-ligand bimetal complex catalyst, the problem of catalyst in the prior art is solved at high temperatures, and efficient catalysis of polyether polyol synthesis at above 200°C is achieved, the process steps are simplified and the process is improved Product quality.
Patent Information
- Application Number
- CN202310198795.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-29
- Filing Date
- 2023-03-03
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-03-03
AI Technical Summary
The existing bimetallic complex catalysts cannot maintain catalytic activity above 200°C, resulting in poor controllability, safety hazards and low product quality in the polyether polyol synthesis process.
Develop a three-ligand bimetallic complex catalyst with a structure of M`a[M``[CN)6]b·(t-BuOH)m·(Poly)n·[M`c(PO4)d ]y, by controlling the type and proportion of ligands, the high temperature thermal stability of the catalyst is improved, so that it maintains catalytic activity within the range of 200-250°C.
High-efficiency catalysis of polyether polyol synthesis above 200°C is achieved, process steps are simplified, reaction time is shortened, and the molecular weight uniformity and mass stability of the product are improved.
Smart Images

Figure CN116217913B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalysts, and in particular to a three-ligand bimetallic complex catalyst and a preparation method thereof. Background Art
[0002] Polyether polyol is an important chemical raw material and an important raw material for synthesizing polyurethane resin products, such as polyurethane foam, polyurethane adhesive, polyurethane elastomer, etc. At present, the bimetallic complex (abbreviated as DMC) catalytic synthesis process is one of the main processes for polyether polyol. The raw material is epoxy compound, DMC has high reaction activity, and the product polyether polyol does not need adsorption and filtration catalyst to achieve residual heavy metal level below 30ppm, which makes DMC catalytic synthesis process more and more concerned in the field of polyether polyol synthesis.
[0003] The reaction of synthesizing polyether polyols catalyzed by a double metal complex (DMC) is an anionic polymerization reaction. For details, see the patent documents China Patent (publication number: CN1145655C), China Patent (publication number: CN103360595A), China Patent (publication number: CN107200837A) and academic journal documents "Mechanism of Propylene Oxide Polymerization Catalyzed by Zinc / Cobalt Double Metal Cyanide Complex" (Liu Xiaohua, Kang Maoqing, Wang Xinkui, Synthetic Rubber Industry. 2001 (24): (03) 147-151), "Research and Discussion on the Catalytic Mechanism of Synthesis of Polyether Polyols Catalyzed by DMC" (Guan Songyun, Li Yusong, Polyurethane Industry. 2011 (06): 1-4.), etc. The reaction mechanism can be summarized as follows:
[0004] (1) Epoxy compounds activate DMC to produce a large number of active centers. This process is the induced activation stage. In order to quickly and completely activate DMC, an initial activation temperature should be given and should not be too high to break the chemical bonds. During the activation process, epoxy compounds will generate a lot of heat due to polymerization, and the reaction controllability is poor. The temperature of the reaction system at this stage is the initial temperature + the temperature of the exothermic rise, which is called the activation temperature;
[0005] (2) After DMC is fully activated, the active center is connected to the chains of many initiators. The epoxy compound as the polymerization monomer is inserted into the vacancy provided by the active center for ring-opening polymerization to achieve polymer chain growth. Then, a substitution reaction occurs between the initiator and the active structure formed by the epoxy compound and the catalyst. The rate of the substitution reaction is higher than the growth rate of the active chain. This process is the polyether chain growth stage. In this process, heat is required from the outside to facilitate rapid chain growth. The temperature of this stage is called the reaction temperature.
[0006] Since the existing DMC catalyst cannot maintain catalytic activity above 200°C, the existing DMC catalytic synthesis process has three major defects, including: (1) Epoxy compounds have low boiling points and high activity, and are prone to random self-polymerization at room temperature, generating a large amount of heat; (2) Once the epoxy compounds are induced to release a large amount of heat, high temperature and pressure are generated in the reactor, and the controllability of the reaction becomes poor. It is not suitable to add too much epoxy compounds at this stage; (3) There is a large amount of heat release in the production of high molecular weight polyether polyols catalyzed by DMC. The three major defects of the DMC catalytic synthesis process are in conflict with the actual conditions that must be met, such as the need to synthesize products of different molecular weights, the production must be safe, and the production must ensure product quality, which makes the DMC catalytic synthesis process subject to relatively fatal limitations.
[0007] The general structural formula of the double metal cyanide (DMC) catalyst disclosed in the Chinese patent (application number CN02113022.1) is M 1 a M 2 (CN) b ] d ·xM 3 (x) c ·wH2O·yT·jP·zA,M 3 is selected from Zn 2+ , Fe 3+ 、Ni 2+ The metal ion, X is selected from Cl - 、SO4 2- , T is tert-butyl alcohol, P is polyether polyol, A is an organosiloxane containing Si-C chain, and the cat activity test obtained in an ideal example in the embodiment is: initiator Mn=416 polyoxypropylene glycol 70g, reaction temperature 105℃, cat8-30ppm, induction time 55min, reaction time 300min, the polyether hydroxyl value is 27.4mgKOH / g, and the viscosity is 950mpa·s (25℃). The double metal cyanide (DMC) catalyst of the patent is a 5-ligand structure, one of which is crystal water and the other is a water-soluble salt. In the invention, in order to avoid the problem of catalyst activity damage when the catalyst is dried in the ordinary process (0-80℃), a more effective catalyst drying method is also proposed for this invention. The double metal cyanide (DMC) catalyst disclosed in the patent must have crystal water in its molecular structure due to the ligand water-soluble salt, so that the catalyst is also easily damaged at the drying temperature of the preparation. The typical reaction temperature of the patent catalytic polymerization reaction is about 105℃.
[0008] The crystalline DMC catalyst disclosed in USP6323375 (Bayer Company) uses tert-butyl alcohol TBA as a complexing agent, contains a functional polymer, 1-10%wt of water, and 25%wt of a water-soluble salt (ZnCl2). The cat activity test obtained in an ideal example in the embodiment is as follows: initiator Mn=1000, polyoxypropylene glycol 50g, reaction temperature 105°C, cat 15ppm, induction time 80min, reaction time 335min, the polyether hydroxyl value 27.4mgKOH / g, viscosity 1084mpa·s (25°C). In the structure of the catalyst in this patent, one ligand is crystal water, and the other ligand is a water-soluble salt, so that in this patent embodiment, in order to avoid catalyst damage, a high-speed homogenization method is used during preparation, the washing process is only once, and the typical reaction temperature of the catalytic polymerization reaction in this patent is 105°C.
[0009] The structural formula of the DMC catalyst disclosed in the US patent (publication number US5158922) is w(DMC).x(L)·yM 1 (X) n ·z(H2O), the patent is a three-ligand catalyst, in which ligand L is an organic substance and ligand M is 1 (X) n It is a water-soluble salt, and the third ligand is crystal water; the typical reaction temperature of the patented catalytic polymerization reaction is 90°C.
[0010] The general structural formula of the DMC catalyst disclosed in the international patent (publication number WO01 / 80994) is Zn3[Co(CN)6]2·xZnCl2·yH2O·zGlyme. This patent is a three-ligand catalyst, in which the ligand Glyme is a polyether polyol, the ligand ZnCl2 is a water-soluble salt, and the third ligand is crystalline water; the typical reaction temperature of the polymerization reaction catalyzed by this patent is 105°C.
[0011] The Chinese patent (application number CN201210156743.9) uses DMC catalyst to react at a temperature of 60-250°C and an absolute pressure of 0.02 bar-100 bar to obtain an alkoxylated product having one or more chemically bonded chlorine atoms. In the embodiment of the patent, the reaction temperature during the catalytic polymerization reaction is only 130°C, and the selected catalyst is only zinc hexacyanocobalt (III) acid. Zinc hexacyanocobalt (III) acid has basically no catalytic activity if it does not have a ligand. Therefore, the DMC catalyst in the patent is not supported by the specification for catalytic reaction at a temperature of 250°C. In order to overcome the three major defects of the DMC catalytic synthesis process, there are currently four technical means that are necessary in the industrial production of polyether polyols. First, the process route of DMC catalytic synthesis of polyether polyols is divided into three steps, and there are clear characteristic marks as boundaries between the three steps. Second, add the epoxy compound with low boiling point and high activity slowly in two times to prevent large amount of heat release from causing high temperature and high pressure in the reactor and increasing the danger; third, control the temperature of the whole process below 200℃ to prevent the mixture from decomposing significantly due to heat; fourth, add most of the initiator after activation to prevent the catalyst from being passivated, reducing the active centers and affecting the formation of the target product.
[0012] From the existing process route, it can be seen that there are many process steps, inconvenient operation process, poor reaction controllability, long process time and other problems. The essence is that the technical personnel in this field have not been able to design a breakthrough solution for the large amount of heat released by epoxy compounds during the reaction process, especially the DMC catalyst cannot maintain catalytic activity above 200°C.
[0013] The dilemma for those skilled in the art is that if the amount of epoxy compound vaporized in the reactor is large, there are safety hazards and it cannot be widely used. However, if the amount of epoxy compound vaporized in the reactor is small, since the DMC catalyst is solid, the activation difficulty increases and the activation center is unevenly distributed, resulting in low quality of the final product. In order to overcome the safety hazards, the conventional solution that those skilled in the art have to adopt is to add the catalyst and an appropriate amount of epoxy compound at room temperature, and use high-speed stirring to make them fully contact in a solid-liquid state. In the entire process of DMC catalytic synthesis of high molecular weight polyether polyols, it is common to control the process temperature within 200°C. The activation temperature is the sum of the initial temperature of the system and the exothermic temperature of the system during the induction activation period. The energy required for the chain growth process in the polyether polyol synthesis process is low, and the temperature peak occurs during the induction activation period. The activation temperature needs to be controlled to ensure that the temperature and pressure in the reactor are not too high; the current process feeding method is slow feeding, so there is a time difference, and the heat generated in the internal activation process is dissipated, which is manifested as a drop in the temperature in the reactor. Therefore, the chain growth period also requires external heating to control the internal temperature of the reactor to allow the reaction to proceed normally. During the entire process, one purpose of controlling the temperature is to prevent the large amount of heat released by a large number of epoxy compounds when synthesizing polyether polyols in large quantities. The reactor cannot dissipate heat in time, resulting in a sudden temperature rise, causing the product to be unqualified or even exceeding the pressure resistance of the reaction equipment, posing a risk of explosion; another purpose of controlling the temperature is to prevent the mixture from decomposing due to heat. The mixture contains catalysts, small molecule polyether polyols, etc. If the activation temperature exceeds the decomposition temperature of the mixture, even if more heat is added later, high molecular weight polyols will not be generated, resulting in unqualified product quality.
[0014] The miniaturization of the reactor can solve the above-mentioned dilemma of technical personnel in the field to a certain extent. For example, in the laboratory test of polyether polyol synthesis reaction, the amount of epoxy compound required is small, the reactor volume is small (within 1L), and when the temperature rises during the activation process, the reaction system has good heat dissipation due to its relatively small volume. The raw materials can be added in a centralized manner to reduce the errors of frequent operations without causing the danger of excessive temperature and pressure due to untimely heat dissipation of the reactor.
[0015] The technical solution provided by the Chinese patent (publication number CN1145655C) is that the amount of alkylene oxide added is controlled at 1-30wt%. Alkylene oxide, i.e., alkylene oxide, is added in two steps. Before the reaction, DMC and inert solvent toluene are added simultaneously, and then part of the alkylene oxide is added. The addition of toluene can increase the heat exchange area and ensure that the activation temperature is between 20-200°C. After the pressure drop is observed, the temperature in the reactor is above 100°C, and the remaining alkylene oxide is added to react. In the post-treatment period, the inert solvent toluene is distilled off at 120°C / 10mbar. It adopts the method of adding an inert solvent to increase the heat exchange area and adding alkylene oxide in two steps or continuously to reduce the induction period, and controls the peak temperature of the entire process within 200°C to ensure safety. However, its induction activation period is characterized by a sudden drop in pressure in the reaction device. In fact, the induction activation period and the chain growth period are two clearly separated steps. In addition to the heating time of the induction activation period, the time for adding the remaining alkylene oxide after the induction activation period is as long as 2.5 hours, and the reaction will not be terminated immediately after the addition (Gao Ming. Optimization and discussion of the production process of DMC-based polyether polyols by intermittent method [C]. / / Proceedings of the 9th Polyester, Polyether Polyol (Propylene Oxide) Scientific Research, Production and Technology Exchange Conference. 2015.). The more raw materials there are, the lower the catalyst concentration will be, which will extend the reaction time. Therefore, the overall reaction time will be much longer than 2.5 hours. In addition, the inert solvent added to increase the heat exchange area also needs to be distilled off in the post-treatment, which increases the burden of post-treatment.
[0016] The miniaturization of the reactor solves the dilemma faced by technicians in the laboratory, but brings an amplification effect in the mass production process. The main reason is that the large-scale synthesis of polyether polyols (number average molecular weight within 2000) or high molecular weight polyether polyols (number average molecular weight above 5000) requires a large number of epoxy compounds, and the heat released in the synthesis reaction is very large. If the heat is not dissipated in time, the product will be unqualified or even exceed the withstand voltage of the reaction equipment, resulting in the risk of explosion. Therefore, in order to control the process temperature, avoid the concentrated release of a large amount of heat by a large amount of epoxy compounds in the reactor, and ensure the safety of the process, the conventional method that the technicians in this field have to adopt is to add an inert solvent to increase the heat exchange area, and to add the epoxy compound in two steps or by continuous injection.
[0017] In summary, the prior art does not have a catalyst that can maintain high temperature activity above 200°C, and in the process of preparing polyether polyols, there is no catalytic polymerization reaction using a bimetallic catalyst above 200°C. In order to efficiently and high-quality large-scale production of high molecular weight polyether polyols, those skilled in the art are in urgent need of a bimetallic complex catalyst that can still maintain catalytic activity above 200°C, so that the catalytic synthesis of polyether polyols can be concentrated in one-time input of reaction raw materials, thereby overcoming the need to distinguish the order of feeding, reducing process steps, and reducing process time. Summary of the invention
[0018] The prior art does not solve the problem of DMC catalyst maintaining high temperature activity above 200°C. Therefore, when DMC catalyst is used to catalyze the preparation of polyether polyols, there are problems such as the need to distinguish the order of feeding, many process steps and long process time. In view of the shortcomings of the prior art, the present invention provides a tri-ligand bimetallic complex catalyst and a preparation method thereof. The obtained tri-ligand bimetallic complex catalyst has high activity and strong heat resistance, and good thermal stability at 200°C-250°C, so that when preparing high molecular weight polyether polyols, the reaction raw materials can be added at room temperature in a centralized manner. The reaction raw materials include DMC tri-ligand bimetallic complex catalyst, initiator and epoxy compound. The one-time centralized addition of reaction raw materials means that all reaction raw materials are added to the reaction device at room temperature, and no reaction raw materials are added during the reaction process. The polymerization reaction can be carried out at a high temperature of more than 200°C. The tri-ligand bimetallic complex catalyst of the present invention has no significant thermal decomposition in the reaction mixture. The tri-ligand bimetallic complex catalyst of the present invention can be used to prepare high molecular weight polyether polyols with a number average molecular weight Mn of 5000-10000.
[0019] The first object of the present invention is to provide a three-ligand bimetallic complex catalyst, wherein the three-ligand bimetallic complex catalyst structure is M' a [M``(CN)6] b ·(t-BuOH) m (Poly) n ·[M` c (PO4) d ] y ,in,
[0020] The first ligand t-BuOH is tert-butyl alcohol,
[0021] The second ligand Poly is selected from polyether polyols or their derivatives with a number average molecular weight Mn of 300 to 2000,
[0022] The third ligand is phosphate,
[0023] The general structural formula of the polyether polyol is represented by formula (I):
[0024]
[0025] In formula (I), the value of e ranges from 0 to 40, the value of f ranges from 0 to 40, the value of e+f ranges from 2 to 45, and R1 to R2 are independently hydrogen atoms or monovalent hydrocarbon groups having 1 to 5 carbon atoms;
[0026] The atomic molar ratio of M` to M`` is 1.5 to 3:1,
[0027] M` is selected from Zn2+ , Fe 3+ 、Ni 2+ Sn 4+ , Pb 2+ ,M`` is selected from Co 3+ , Fe 3+ , Ir 3+ ,
[0028] a, b, c, d are ionic coefficients, satisfying the balance of positive and negative charges, m, n, y are any positive numbers,
[0029] The weight proportions of the ligands are:
[0030] The weight of the first ligand t-BuOH is 0.05 to 10% of the total weight of the three-ligand bimetallic complex catalyst;
[0031] The weight of the second ligand Poly is 5 to 20% of the total weight of the tri-ligand bimetallic complex catalyst;
[0032] The weight of the third ligand phosphate is 4 to 30% of the total weight of the three-ligand bimetallic complex catalyst;
[0033] Preferably, the atomic molar ratio of M` to M`` is 1.65 to 2.54:1;
[0034] Preferably, the weight of the first ligand t-BuOH is 3-8% of the total weight of the tri-ligand bimetallic complex catalyst; the weight of the second ligand Poly is 8-15% of the total weight of the tri-ligand bimetallic complex catalyst; the weight of the third ligand phosphate is 4-25% of the total weight of the tri-ligand bimetallic complex catalyst.
[0035] Wherein, m, n, and y are the first ligand system number, the second ligand system number, and the third ligand system number, respectively, and their values are related to the total weight of the three-ligand bimetallic complex catalyst, the type of metal ions, and the weight of each ligand. The values are derived and calculated based on the test data. The specific derivation and calculation method is as follows:
[0036] After the catalyst is prepared in the present invention, the atomic molar ratio of M` to M`` is detected by inductively coupled plasma spectrometry (ICP). When the atomic molar ratio of M` to M`` is known, since M` exists in M` a [M``(CN)6] b and the third ligand [M` c (PO4) d ] y , M`` only exists in M` a [M``(CN)6] b Therefore, the value of the third ligand system constant y can be calculated;
[0037] It is known that metal structure compounds have high heat resistance, so the final remaining weight in the thermal weight loss experiment is the metal structure compound M` a [M``(CN)6] b ·[M` c (PO4) d ] y From the previous description, we know that the structural molecular formula and its weight ratio are known, so we know that the three-ligand bimetallic complex catalyst (M` a [M``(CN)6] b ·(t-BuOH) m (Poly) n ·[M` c (PO4) d ] y ) molecular weight. Among them, the first ligand tert-butyl alcohol has poor heat resistance, so the weight loss in the first stage is its thermal behavior, and its weight proportion can be seen from the thermal weight loss diagram (see Figure 1 ) is obtained, the molecular weight of the three-ligand bimetallic complex catalyst, the proportion of the first ligand and the molecular weight are known, so the m value is calculated; the second ligand has a large molecular weight and enhanced heat resistance, so the second section is its thermal behavior, and its weight proportion can also be obtained from the thermogravimetric diagram (see Figure 1 ) It is concluded that the molecular weight of the three-ligand bimetallic complex catalyst, the proportion of the second ligand and the molecular weight are known, so the value of n is calculated; for the weight of the phosphate ion measured by ion chromatography, the most important thing is to verify the molecular formula of the three-ligand bimetallic complex catalyst, and another function is to help calculate the molecular formula of the bimetallic catalyst when the two metals are the same.
[0038] Preferably, the derivative of the polyether polyol is a carbon dioxide-based polycarbonate-polyether polyol, referred to as PCEL in English, and its general structural formula is represented by formula (II):
[0039]
[0040] In formula (II), the value of e ranges from 2 to 23, the value of f ranges from 0 to 13, the value of e+f ranges from 2 to 25, and the number average molecular weight Mn of the second ligand PCEL is 300 to 2000. The difference between the structure of polyether polyol and PCEL is that the value of e in formula (II) is zero, that is, it does not contain carbonate bonds. The increase of carbonate bonds increases the hydrogen bonding effect of the polymer, enhances the electron cloud density on the molecular chain, can improve the coordination ability, and improve the resistance to thermal decomposition.
[0041] Preferably, the three-ligand bimetallic complex catalyst is structurally stable at 200-250° C. in an inert atmosphere, and the high-temperature thermal stability coefficient L is ≤1.2%. The inert atmosphere refers to a gas that does not have an oxidizing property. The high-temperature thermal stability coefficient L is calculated as follows:
[0042]
[0043] m% refers to the residual mass percentage at the temperature corresponding to any point on the thermogravimetric curve, T1 and T2 are the temperatures corresponding to any point on the thermogravimetric curve, T1 and T2 are in the range of 200 to 250°C, T1>T2; preferably, T1 and T2 are in the range of 220 to 250°C, respectively;
[0044] Preferably, the tri-ligand bimetallic complex catalyst is structurally stable at 220-250°C in an inert atmosphere. At high temperatures, if the mass loss is too high, the structure is severely damaged, which will lead to catalyst deactivation. A slight mass reduction may remove impurities remaining inside the catalyst structure and expose more active sites. The high temperature described in the present invention refers to a temperature above 200°C, and in particular, may refer to a temperature of 220-250°C.
[0045] Preferably, the tri-ligand bimetallic complex catalyst is in the shape of an irregular sphere.
[0046] Preferably, the specific surface area of the three-ligand bimetallic complex catalyst is 300 to 570 m 2 / g, the specific surface area can be obtained according to the BET calculation method.
[0047] The second object of the present invention is to provide a method for preparing the above-mentioned three-ligand bimetallic complex catalyst, comprising the following steps:
[0048] 1) Weigh a soluble metal salt of metal ion M` and a soluble metal cyanide complex salt of metal ion M`, and dissolve them in tert-butyl alcohol-water solution and deionized water respectively. After being evenly dispersed, add them into a reaction device and stir them evenly to obtain a metal cyanide complex solution system. Then, under the conditions of a reaction temperature of 70 to 90° C. and a reaction time of 2 to 6 hours, a complex reaction occurs in the metal cyanide complex solution system to form M`. a [M``(CN)6] b ·(t-BuOH) m structure;
[0049] Wherein, the metal ion M' is selected from Zn 2+ , Fe 3+ 、Ni 2+ Sn 4+ , Pb 2+ , the metal ion M is selected from Co 3+ , Fe 3+ , Ir 3+ ,
[0050] The ratio of the molar number of the soluble metal cyanide complex salt to the molar number of the soluble metal salt when dissolved is 1:2-5.
[0051] The volume ratio concentration of the tert-butyl alcohol-water solution is 40-98%. In the cyanide metal complex solution system, the weight concentrations of the soluble cyanide metal complex salt and the soluble metal salt are 10%-40wt% respectively. The soluble cyanide metal complex salt and the soluble metal salt do not need to be completely dissolved in the tert-butyl alcohol-water solution, and can be partially dissolved therein.
[0052] (2) After step (1) is completed, heating is stopped, and Poly, phosphoric acid or its derivatives are added to the reaction device, and the residual heat of the reaction in step (1) is used to react until the temperature drops to room temperature to form M` a [M``(CN)6] b ·(t-BuOH) m (Poly) n ·[M c `(PO4) d ] y Ligand structure;
[0053] (3) After step (2), the material is filtered and then washed with a tert-butyl alcohol-water solution to remove unreacted metal ions and uncoordinated Poly and phosphoric acid or its derivatives, and then vacuum dried to obtain a tri-ligand bimetallic complex catalyst;
[0054] Preferably, the soluble cyanide metal complex salt of the metal ion M`` is selected from potassium hexacyanocobaltate, sodium hexacyanocobaltate, potassium hexacyanoferrate (III) or zinc hexacyanoiridate (III), preferably potassium hexacyanocobaltate;
[0055] Preferably, the soluble metal salt of the metal ion M' is selected from zinc chloride, zinc bromide, ferric chloride, nickel chloride, tin chloride, and lead chloride, preferably zinc chloride;
[0056] Preferably, the phosphoric acid derivative is selected from any one of potassium hydrogen phosphate, sodium hydrogen phosphate, potassium dihydrogen phosphate, sodium dihydrogen phosphate, sodium pyrophosphate, acidic sodium pyrophosphate, and metaphosphoric acid;
[0057] Preferably, in step (1), the molar ratio of the metal cyanide complex salt to the soluble metal salt substance added to the reaction device is 1:2-4;
[0058] Preferably, the volume ratio concentration of the tert-butyl alcohol-water solution is 50 to 90%;
[0059] Preferably, in step (1), the weight concentrations of the soluble metal cyanide complex salt and the soluble metal salt are 15% to 25wt% respectively;
[0060] Preferably, in step (2), the Poly and M are fed a [M``(CN)6] b The weight ratio of the structure is 5 to 20:100, preferably 10 to 15:100,
[0061] In step (2), the phosphoric acid or its derivative added as feed material is reacted with M' a [M``(CN)6] b The weight ratio of the structure is 5 to 20:100, preferably 5 to 10:100;
[0062] Preferably, in step (1), the reaction temperature is 80-85° C. and the reaction time is 3-5 hours;
[0063] Preferably, in step (3), the volume ratio concentration of the tert-butyl alcohol-water solution is 50-90%; the vacuum drying method is vacuum high temperature drying or vacuum freeze drying; more preferably, the vacuum drying method is vacuum freeze drying.
[0064] M` a [M``(CN)6] b The weight content of the structure can be obtained by theoretical calculation based on the amount of the soluble metal cyanide complex salt of the metal ion M` and the soluble metal salt of the metal ion M`` added in step (1), because M` a [M``(CN)6] b The significance of the basic theoretical value of structural calculation is that the chemical structure is a fixed structure. After feeding, the weight content of M` and M`` can be determined. a [M``(CN)6] b The chemical molecular weight has been determined; M` a [M``(CN)6] b The weight content of the structure can also be detected in the cyanide metal complex solution system obtained in step (1) a [M``(CN)6] b The structural content can be obtained by combining thermogravimetric analysis with inductively coupled plasma spectroscopy (ICP).
[0065] The third object of the present invention is to provide a use of the tri-ligand bimetallic complex catalyst as described above or the tri-ligand bimetallic complex catalyst prepared by the preparation method as described above in a chemical reaction; preferably, the chemical reaction is a polymerization reaction, and the polymerization reaction is a reaction in which an epoxy compound participates; more preferably, the chemical reaction is a reaction in which an epoxy compound participates in preparing a polyether polyol.
[0066] The technical solution of the present invention has the following beneficial effects:
[0067] (1) The tri-ligand bimetallic complex catalyst DMC of the present invention has a stable structure in an inert atmosphere at high temperature (high temperature>200°C), and a high temperature thermal stability coefficient of less than or equal to 1.2% at 200-250°C. The DMC catalyst of the present invention has a stable structure in an inert atmosphere at a high temperature greater than 200°C, and has strong anti-deactivation performance, so that the reaction raw materials can be put into a large-scale production reactor equipment (10L≤reactor internal volume≤100L) to produce high molecular weight polyether polyols at one time, and the reaction is carried out at above 200°C. Since the tri-ligand bimetallic complex catalyst DMC of the present invention does not significantly decompose when heated during the reaction process, the requirements for the initiator are low, and thus there is no obvious amplification effect. Since the induction activation period and the segment growth period can be combined into one step, the use of the tri-ligand bimetallic complex catalyst DMC of the present invention can not only significantly shorten the polymerization reaction process time, but also simplify the production process.
[0068] (2) When the tripartite bimetallic complex catalyst DMC of the present invention is used to catalyze the preparation of high molecular weight polyether polyols, the tripartite bimetallic complex catalyst DMC of the present invention exhibits improved water resistance, excellent heat resistance, and high resistance to deactivation. Therefore, the tripartite bimetallic complex catalyst DMC of the present invention can be fed simultaneously with various initiators (powder or liquid) and epoxy compounds, and there is no need to induce activation of the catalyst. The uniformity of the polymerization reactants in the polymerization reaction system can be improved, so that the tripartite bimetallic complex catalyst DMC of the present invention can be activated to induce the generation of a large number of active centers.
[0069] (3) The three-ligand bimetallic complex catalyst DMC of the present invention has high catalytic activity and is suitable for a variety of initiators. It can synthesize a variety of polyether polyols obtained from different initiators, and the molecular weight is stable at 5000-10000. Therefore, the application of the three-ligand bimetallic complex catalyst DMC of the present invention can prepare a wider range of polyether polyol products, and it is more convenient for the polyether polyol products to be further used in the synthesis of polyurethanes with different molecular weights. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 It is a thermogravimetric diagram of the DMC-1 catalyst of Example 1 of the present invention and the commercially available DMC-CK1 catalyst of Comparative Example 1, in which A, B, C, D, and E respectively represent the intersection points of the DMC-1 catalyst of the present invention with the thermogravimetric curve at 100°C, 200°C, 250°C, 265.6°C, and 400°C, and A`, B`, C`, D`, and E` respectively represent the intersection points of the commercially available DMC-CK1 catalyst with the thermogravimetric curve at 100°C, 200°C, 250°C, 265.6°C, and 400°C.
[0071] Figure 2 This is a microscopic morphology image of DMC-1 of Example 1 of the present invention.
[0072] Figure 3 This is the adsorption-desorption isotherm diagram of the DMC-1 catalyst of the present invention in nitrogen.
[0073] Figure 4 This is the pore size distribution diagram of the DMC-1 catalyst of the present invention. DETAILED DESCRIPTION
[0074] Test methods for each performance:
[0075] M` and M`` atomic molar ratio detection:
[0076] Inductively coupled plasma spectrometry (ICP) was used for detection. Accurately weigh 0.1000g of the catalyst and put it into a glass beaker. Pour 30mL of aqua regia into the beaker. Heat the beaker to 80°C on a graphite heating plate. After the liquid becomes colorless and transparent with no obvious solid, remove it and cool it down. Then, dilute it with pure water. The metal content in the aqueous solution was measured with an ICP instrument to obtain the atomic molar ratio of M` to M``.
[0077] The first ligand t-BuOH and M` a [M``(CN)6] b ·(t-BuOH) m (Poly) n ·[M c `(PO4) d ] y Weight ratio test of structure:
[0078] Thermogravimetric method was used for detection. The three-ligand bimetallic complex catalyst sample was placed in the reactor, protected by nitrogen, and heated to a temperature range of 300-400°C at a rate of 10°C / min. After the test was completed, the weight ratio of the first ligand t-BuOH of the corresponding substance was calculated according to the different stages of the thermogravimetric curve. On the thermogravimetric curve under nitrogen protection, see Figure 1 , tert-butyl alcohol has a low boiling point, and the first stage is the weight loss behavior of the first ligand t-BuOH. Because DMC is a porous powder with a large specific surface area, it is easy to absorb tiny particles or moisture in the air. It should be stored under vacuum drying, otherwise it will affect the quality of the first ligand in the first stage; the final residual weight is the inorganic compound M` a [M``(CN)6] b ·[M c `(PO4) d ] y The weight of the structure.
[0079] The second ligand Poly and M` a [M``(CN)6] b ·(t-BuOH) m (Poly)n ·[M c `(PO4) d ] y Weight ratio test of structure:
[0080] Thermogravimetric method was used for testing. The catalyst sample was placed in the reactor and protected with nitrogen. The temperature was raised to 300-400°C at a rate of 10°C / min. After the test was completed, the weight ratio of the second ligand Poly of the corresponding substance was calculated according to the different stages of the thermogravimetric curve. The weight ratio of the second ligand Poly of the corresponding substance was calculated according to the thermogravimetric curve of nitrogen protection (see Figure 1 ), tert-butyl alcohol has a low boiling point, and the first stage is the weight loss behavior of the first ligand t-BuOH; the decomposition temperature of the second ligand Poly under anaerobic conditions exceeds 200°C, so the second stage is the weight loss behavior of the second ligand Poly, and the final residual weight is the inorganic compound M` a [M``(CN)6] b ·[M c `(PO4) d ] y The weight of the structure.
[0081] The third ligand M c `(PO4) d With M` a [M``(CN)6] b ·(t-BuOH) m (Poly) n ·[M c `(PO4) d ] y Weight ratio test of structure:
[0082] Ion chromatography was used. 10g of catalyst was digested with nitric acid and then prepared into 500mL solution. If the solution contained two metal ions, the phosphate test method in HJ669-2013 should be referred to. After the two metal ions were exchanged, the solution did not contain metals. The phosphate concentration ρ (mg / L) was obtained by ion chromatography. By formula (Ⅰ)
[0083] Weight ratio (phosphate) = salt formula chromatograph -3 / (95*10 / MW)*100% formula (Ⅰ)
[0084] Where 500 refers to the solution volume, 95 is the molecular weight of the phosphate group, 10 is the mass of the catalyst, and MW is M c `(PO4) d Molecular weight.
[0085] Shape detection of tri-ligand bimetallic complex catalysts:
[0086] Scanning electron microscope observation was used. The catalyst was ultrasonically dispersed in ethanol, then dropped on tin foil, and then vacuum-sprayed with gold at 10 mA for 30 seconds. Then, it was taken out and placed under an electron microscope to observe the morphology.
[0087] Specific surface area detection of tri-ligand bimetallic complex catalyst:
[0088] The test was conducted using the Quantachrome automatic gas adsorption system (AUTOSORB-1-C) of the full adsorption instrument, and the specific surface area was calculated using the N2 adsorption curve of the BET technique. Before the test, the catalyst was treated at 200°C in vacuum for 1 hour to prevent dust or water adsorbed in the pores from affecting the test results.
[0089] Detection of number average molecular weight Mn:
[0090] The specific test conditions were as follows: the gel chromatography column was a PLgelMixed-C column (300 mm×4.5 mm, 5 μm); the column temperature was 40°C; the mobile phase was tetrahydrofuran with a flow rate of 1 mL / min; the injection volume was 100 μL; and the analysis time was 20 min.
[0091] Volatile organic compound (VOC) content detection:
[0092] Volatile organic compounds are usually expressed as VOC, and their total content is sometimes expressed as TVOC. There is no unified definition of VOC, but according to the definition of the World Health Organization, it is a general term for volatile organic compounds with a melting point below room temperature and a boiling point between 50 and 260°C. The PID detector (portable VOC detector) is a non-destructive detector that does not change the gas molecules to be tested and achieves continuous real-time detection. The method of use is: turn on the power, check the battery power, and meet the specified requirements. Check whether the indication is zero in clean air. If it is not zero, a fault check is required; if it is zero, you can take it to the working space and use it to check the indication. After use, come to the clean air again to observe that the indication is 0 and then turn off the power.
[0093] The polydispersity index (PDI) of polyether polyols was measured by gel permeation chromatography.
[0094] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0095] Synthesis of DMC Catalysts Using Tri-ligand Bimetallic Complexes
[0096] Example 1
[0097] The purpose of Example 1 is to prepare the tri-ligand bimetallic complex catalyst DMC of the present invention through the preparation method of the present invention, detect the prepared tri-ligand bimetallic complex catalyst DMC, and characterize its performance.
[0098] Example 1 is to prepare a structure M' a [M``(CN)6] b ·(t-BuOH) m (Poly) n ·ol c `(PO4) d ] y The tri-ligand bimetallic complex catalyst, M' is selected from Zn, Fe, Ni, Sn, Pb, M'' is selected from Co, Fe, Ir, the atomic molar ratio of M' to M'' is 1.5-3:1, preferably, the atomic molar ratio of M' to M'' is 1.65-2.54:1. The atomic molar mass of Zn is 65.38, valence +2, the atomic molar mass of Fe is 55.845, valence +3, the atomic molar mass of Ni is 58.69, valence +2, the atomic molar mass of Sn is 118.71, valence +4, the atomic molar mass of Pb is 207.2, valence +2, the atomic molar mass of Co is 58.9332, valence +3, and the atomic molar mass of Ir is 192.22, valence +3.
[0099] In this embodiment, the selected M` is different from M``, and the atomic molar ratio of M` to M`` is 1.5-3:1. The soluble metal cyanide complex salt of the metal ion M`` is selected from potassium hexacyanocobaltate, sodium hexacyanocobaltate, potassium hexacyanoferrate (III), or zinc hexacyanoiridate (III), preferably potassium hexacyanocobaltate. In this embodiment, the cyanide metal complex salt is selected from potassium hexacyanocobaltate; the soluble metal salt of the metal ion M` is selected from zinc chloride, zinc bromide, ferric chloride, nickel chloride, tin chloride, and lead chloride. In this embodiment, zinc chloride is more specifically preferred, and the soluble metal salt is zinc chloride. Polyether polyol or its derivative, in this embodiment, its derivative carbon dioxide-based polyester polyether polyol (PCEL) is preferred, which becomes the second ligand in the order of addition time. The phosphoric acid derivative is selected from any one of potassium hydrogen phosphate, sodium hydrogen phosphate, potassium dihydrogen phosphate, sodium dihydrogen phosphate, sodium pyrophosphate, acidic sodium pyrophosphate, and metaphosphoric acid. In this embodiment, phosphoric acid is more specifically preferred to obtain the third ligand M` c (PO4) d It is Zn3(PO4)2.
[0100] The atomic molar ratio of M` to M`` in the three-ligand bimetallic complex catalyst DMC of this embodiment is 1.5 to 3:1, which is preliminarily determined by controlling the ratio of potassium hexacyanocobaltate and zinc chloride fed, and then the type and specific amount of polyether polyol or its derivative, phosphoric acid or its derivative are further added to perform precise control, thereby controlling both the atomic molar ratio of M` to M`` and the atomic molar ratio of the second and third ligands in the catalyst structure (M` a [M``(CN)6] b ·(t-BuOH) m (Poly) n ··[M` c (PO4) d ] y ) by weight ratio, thereby obtaining the required three-ligand bimetallic complex catalyst DMC.
[0101] The weight of the first ligand t-BuOH is 0.05-10% of the total weight of the tri-ligand bimetallic complex catalyst, preferably 3-8%. Specifically, in this embodiment, a cyanide metal complex salt solution is first prepared, and the dispersion medium is deionized water. Then a tert-butyl alcohol-water solution is prepared, and then the solute is a soluble metal salt, stirred evenly, and then the two solutions are mixed evenly. The first ligand t-BuOH, by controlling the concentration of tert-butyl alcohol and the reaction temperature, achieves the control of the first ligand t-BuOH of the tri-ligand bimetallic complex catalyst and the total weight ratio of the catalyst.
[0102] The weight of the second ligand is 5-20%, preferably 8-15%, of the total weight of the three-ligand bimetallic complex catalyst. The second ligand is selected from polyether polyols with a number average molecular weight Mn of 300-2000 or its derivatives.
[0103] The general structural formula of the polyether polyol is represented by formula (I):
[0104]
[0105] In formula (I), the value of e ranges from 0 to 40, the value of f ranges from 1 to 40, the value of e+f ranges from 2 to 40, and R1 to R2 are independently hydrogen atoms or monovalent hydrocarbon groups having 1 to 5 carbon atoms; preferably, the second ligand Poly is a derivative of a polyether polyol, a carbon dioxide-based polycarbonate-polyether polyol (PCEL), and the general structural formula of the carbon dioxide-based polycarbonate-polyether polyol (PCEL) is represented by formula (II):
[0106]
[0107] In formula (II), the value of e ranges from 2 to 23, the value of f ranges from 0 to 13, the value of e+f ranges from 2 to 25, and the number average molecular weight Mn of the second ligand PCEL is 300 to 2000.
[0108] Specifically, in this embodiment, by controlling the molecular structure of Poly, adjusting the performance, complexing quantity and complexing tightness of the second ligand in the three-ligand bimetallic complex catalyst, the three-ligand bimetallic complex catalyst is peripherally complexed with a number of straight or branched long chains, the shape of the three-ligand bimetallic complex catalyst is controlled to be an irregular sphere, and the specific surface area of the three-ligand bimetallic complex catalyst is controlled to be 300-570m 2 / g, so that when the three-ligand bimetallic complex catalyst is used to catalyze the polymerization reaction to form polyether polyols, in the reaction system, the second ligand of the three-ligand bimetallic complex catalyst has excellent dispersibility due to its long-chain structure and can withstand higher temperatures. The second ligand is similarly compatible with the product of the polymerization reaction, the polyether polyol, so that in the polymerization reaction, the catalyst is not easy to form a local enrichment situation. The three-ligand bimetallic complex catalyst also has a small molecule short chain first ligand t-BuOH, so that in the middle and late stages of the polymerization reaction, when the molecular weight of the polyether polyol generated by the polymerization reaction is thickened, it can still have good catalytic performance. In addition, the inventors also unexpectedly found that due to the excellent heat resistance of the three-ligand bimetallic complex catalyst of the present invention, on the one hand, the efficiency of the polymerization reaction is improved, and on the other hand, because at a higher temperature, even if the molecular weight of the polyether polyol is high, the viscosity of the reaction liquid system is still low, and the prepared polyether polyol has a lower molecular weight polydispersity index (PDI).
[0109] The weight of the third ligand phosphate is 4-30% of the total weight of the three-ligand bimetallic complex catalyst, preferably 4-25%; more specifically, phosphoric acid or its derivatives, preferably phosphoric acid. Phosphate has a high charge and can form a precipitate with heavy metals to improve heat resistance.
[0110] The preparation method of the three-ligand bimetallic complex catalyst of this embodiment comprises the following steps:
[0111] (1) Weighing a soluble metal salt of a metal ion M` and a soluble metal cyanide complex salt of a metal ion M`, respectively dissolving them in a tert-butyl alcohol-water solution and deionized water, adding them to a reaction device after being evenly dispersed, and evenly stirring to obtain a metal cyanide complex solution system, and then causing a complex reaction in the metal cyanide complex solution system at a reaction temperature of 70 to 90° C. and a reaction time of 2 to 6 hours to form M` a [M``(CN)6] b ·(t-BuOH) mstructure; the ratio of the molar number of the soluble cyanide metal complex salt to the molar number of the soluble metal salt when dissolved is 1:2-5. The concentration of the tert-butyl alcohol-water solution is 40-98% (volume ratio), and in the cyanide metal complex solution system, the sum of the weight concentrations of the soluble cyanide metal complex salt and the soluble metal salt is 10%-40wt%;
[0112] (2) After step (1) is completed, heating is stopped, and Poly, phosphoric acid or its derivatives are added to the reaction device, and the residual heat of the reaction in step (1) is used to react until the temperature drops to room temperature to form M` a [M``(CN)6] b ·(t-BuOH) m (Poly) n ·[M` c (PO4) d ] y Ligand structure;
[0113] (3) After step (2), the material is filtered and then washed with a tert-butyl alcohol-water solution to remove unreacted metal ions and uncoordinated Poly and phosphoric acid or its derivatives, and then vacuum dried to obtain a tri-ligand bimetallic complex catalyst;
[0114] Specifically, in this embodiment, the molar ratio of the cyanide metal complex salt to the soluble metal salt is 1:4, the volume concentration of the tert-butyl alcohol aqueous solution is 50%, and when feeding, the feeding amount of Poly is the same as M` a [M``(CN)6] b The weight ratio of the structure is 15:100, phosphoric acid or its derivatives are fed to M` a [M``(CN)6] b The weight ratio of the structure is 10:100, M` a [M``(CN)6] b The weight of the structure is calculated theoretically based on the amount of soluble metal cyanide complex salt of metal ion M` and soluble metal salt of metal ion M``, because M` a [M``(CN)6] b The significance of the basic theoretical value of structural calculation is that the chemical structure is a fixed structure. After feeding, the weight content of M` and M`` can be determined. a [M``(CN)6] b The chemical molecular weight of a [M``(CN)6] b ·(t-BuOH) m (Poly) n ·[M c `(PO4)d ] y The reason for calculating the dosage of various ligands by structure is that there are differences between the structures of the complexes. It is a non-stoichiometric compound with different molecular weights and cannot be accurately estimated. Its relatively accurate molecular weight can only be concluded by detection methods. However, this is not uncontrollable. The stability of the catalyst structure can be achieved by controlling the reaction raw materials and the reaction process. In actual practice, the former is more convenient to calculate, and the latter has a higher content accuracy. In large-scale production, the latter may be more valuable for guidance.
[0115] In this embodiment, in the metal cyanide complex solution system of step (1), the weight concentration of the soluble metal cyanide complex salt and the soluble metal salt is 10% to 40wt%; more specifically, 15% to 25wt%; more specifically, in the metal cyanide complex solution system of step (1). Specifically, in this embodiment, in step (1), the reaction temperature is 80 to 85°C, the reaction time is 3 to 5 hours, more specifically, the reaction temperature is 85°C, and the reaction time is 4h.
[0116] (2) After step (1) is completed, heating is stopped, PCEL and phosphoric acid are added to the reaction device, and the residual heat of the reaction in step (1) is used to react until the temperature drops to room temperature to form M` a [M``(CN)6] b ·(t-BuOH) m (PCEL) n ·[M` c (PO4) d ] y In this embodiment, specifically, after step (1) is completed, heating is stopped, PCEL and phosphoric acid are added to the reaction device, and when adding the materials, PCEL and M` a [M``(CN)6] b The weight ratio of the structure is 5 to 20:100, preferably 8 to 15:100, and in this embodiment, specifically 15:100. Phosphoric acid and M' a [M``(CN)6] b The weight ratio of the structure is 5-30:100; preferably 6-25:100; in this embodiment, specifically 10:100.
[0117] (3) After step (2), the material is filtered and then washed with an aqueous solution of tert-butyl alcohol to remove unreacted metal ions, uncoordinated polyether polyols and inorganic compounds containing phosphorus elements, and then vacuum dried to obtain a tri-ligand bimetallic complex catalyst; in this embodiment, specifically, the vacuum drying method is vacuum high temperature drying or vacuum freeze drying, and the vacuum drying method is preferably vacuum freeze drying.
[0118] In this embodiment, 332g potassium hexacyanocobaltate (about 1mol) was weighed and dissolved in deionized water to prepare 20%wt solution A; 544g zinc chloride (about 4mol) was weighed and dissolved in 50% (v / v) tert-butyl alcohol aqueous solution to prepare 20%wt solution B, wherein the zinc-cobalt ratio was 4:1. Solution B was stirred rapidly at a speed of 600r / min, and solution A was added dropwise thereto. After the addition was completed, the temperature was set to 85°C, and the heating was stopped after heating for 4h. 48.75g of carbon dioxide-based polycarbonate-polyether polyol (Mn=2000) (accounting for 15% of the theoretical weight of Zn3[Co(CN)6]2) and 32.5g of phosphoric acid (accounting for 10% of the theoretical weight of Zn3[Co(CN)6]2) were weighed separately, and dropped into the reaction solution, and stirring was continued for 1 hour. After the end, it was cooled to room temperature. The catalyst solution cooled to room temperature was washed and filtered several times with tert-butyl alcohol aqueous solution to wash out the unreacted raw materials. After four times, there was no potassium ion. It was vacuum dried at 110° C. for 12 h, taken out for use, and recorded as DMC-1.
[0119] The catalytic performance of DMC-1 was tested and the obtained characterizations were as follows:
[0120] (1) Molar ratio of zinc to cobalt: The atomic molar ratio of zinc to cobalt was measured by inductively coupled plasma spectrometry (ICP). In Example 1, the atomic molar ratio of zinc to cobalt was 2.25:1.
[0121] (2) The weight ratio of the first ligand to the second ligand in the catalyst
[0122] Thermogravimetric analysis was performed to analyze the thermogravimetric curve (see Figure 1 ), calculate the high temperature thermal stability coefficient of the catalyst according to the high temperature thermal stability coefficient L calculation formula:
[0123]
[0124] m% refers to the residual mass percentage at the temperature corresponding to any point on the thermogravimetric curve, T1 and T2 are the temperatures corresponding to any point on the thermogravimetric curve, T1 and T2 are in the range of 200 to 250°C, T1>T2; preferably, T1 and T2 are in the range of 220 to 250°C, respectively;
[0125] The temperature is between 200-250°C, and the high temperature thermal stability coefficient is 1.2%. The first ligand, tert-butyl alcohol, has a low boiling point and is lost first under nitrogen protection. At point D (complete loss, the temperature is 265.6°C, and the mass is 94.2%, and the weight loss is 5.8%, that is, the mass ratio of t-BuOH to the three-ligand bimetallic complex catalyst is 5.8%; the second ligand, carbon dioxide-based polycarbonate-polyether polyol, has a decomposition temperature of more than 200°C under anaerobic conditions, and the decomposition temperature of inorganic substances is usually above 500°C, so the next is the decomposition weight loss of carbon dioxide-based polyester polyether polyol, which is completely lost at point E. The residual amount is 83.37% within 400°C, so the second ligand accounts for (100%-83.37%-5.8%=) 10.83% of the catalyst weight.
[0126] (3) The weight ratio of the third ligand Zn3(PO4)2 to the catalyst
[0127] Using ion chromatography, phosphate (PO4) was obtained according to the working curve. 3- The concentration is 0.937 mg / L, and according to the formula, the proportion of the third ligand in the catalyst is 19%.
[0128] (4) The morphology of the three-ligand bimetallic complex catalyst was observed by scanning electron microscopy. Figure 2 It can be seen that the three-ligand bimetallic complex catalyst is irregularly spherical in shape with different sizes, generally less than 5 microns, and some of them are agglomerated.
[0129] (4) The adsorption and desorption isotherms of the DMC-1 catalyst of the present invention in nitrogen are shown in Figure 3 Among the six isotherms classified by IUPAC, it is more in line with Type II; this type of isotherm reflects the typical physical adsorption process on non-porous or macroporous adsorbents, which is the most commonly described object of the BET formula; this indicates that there is a strong interaction on the surface of the DMC-1 catalyst of the present invention, and a large amount of epoxy compounds can be adsorbed and chemically reacted after sufficient contact with the initiator.
[0130] (5) The pore size distribution diagram of the DMC-1 catalyst of the present invention is shown in Figure 4 As can be seen from the figure, the pore size is concentrated in the mesopore and micropore range of less than 20 microns, with a high specific surface area, which is reflected in the large contact area with other reactants. Under such a morphology, the adsorption capacity is large, which helps to improve the catalytic activity; the specific surface area of the three-ligand bimetallic complex catalyst is detected by the Quantachrome automatic gas adsorption system (AUTOSORB-1-C) of the full adsorption instrument, and the specific surface area is determined by the BET formula to calculate the N2 adsorption curve to be 393m 2 / g.
[0131] In summary, it can be seen that in Zn3[Co(CN)6]2·[Zn3(PO4)2]y, Zn:Co=2.25:1, so y=0.5, the molecular weight of the structure is 841.3, and the mass accounts for 83.37%, so the total molecular weight of DMC-1 is 841.3 / 83.37%=1009.1. It is known that the first ligand tert-butyl alcohol accounts for 5.8%, so the molar number is 1009.1*5.8% / 74=0.79. Similarly, the molar number of the second ligand PCEL is 0.055. The mass of 0.5 mol zinc phosphate accounts for the mass of DMC-1 = 192.5 / 1009.1=19%, which is consistent with the measured data, proving that the calculation of this method is correct. It is known that the structural formula of the bimetallic catalyst DMC prepared by this implementation is Zn3[Co(CN)6]2·(t-BuOH) 0.79 (PCEL) 0.055 ·[Zn3(PO4)2] 0.5 .
[0132] Example 2
[0133] The purpose of Example 2 is to select a polyether polyol with a number average molecular weight Mn of 300 to 2000 as the second ligand Poly. The key difference between Example 2 and Example 1 is that Example 2 selects a polyether polyol (English abbreviation PPG) with a number average molecular weight Mn of 1000 to prepare a three-ligand bimetallic complex catalyst DMC, and the preparation method is basically the same as that of Example 1.
[0134] More specifically, in this embodiment, R1 of the polyether polyol is a hydrogen atom, and R2 is a hydrogen atom. The purpose of selecting PPG is to increase flexibility and facilitate the increase of the specific surface area of the catalyst. The polyether polyol has an e value range of 0 to 22, an f value range of 0 to 22, and an e+f value range of 15 to 25. By controlling the number average molecular weight and specific amount of the PPG fed, the composition structure parameter n of the three-ligand bimetallic complex catalyst DMC is controlled to account for 5-20% of the total weight of the catalyst.
[0135] More specifically, in this embodiment, the selected M` is the same as M``. In this embodiment, more specifically, the cyanide metal complex salt is potassium hexacyanoferrate (III); the soluble metal salt of the metal ion M` is ferric chloride, the weight concentration of the soluble cyanide metal complex salt and the soluble metal salt are 20wt% respectively, the volume percentage concentration of the tert-butyl alcohol aqueous solution is 50%, and the ratio of the molar number of the soluble cyanide metal complex salt to the molar number of the soluble metal salt is 1:4. This ratio is the ratio before synthesis, not the metal ratio in the synthesized catalyst. A phosphoric acid derivative is selected to replace the phosphoric acid in Example 1, selected from any one of potassium hydrogen phosphate, sodium hydrogen phosphate, potassium dihydrogen phosphate, sodium dihydrogen phosphate, sodium pyrophosphate, acidic sodium pyrophosphate, and metaphosphoric acid. In this embodiment, more specifically, pyrophosphoric acid is used to obtain the third ligand M`(PO4)x It is FePO4.
[0136] The preparation method of this embodiment is basically the same as that of embodiment 1, except that PPG is fed to the a [M``(CN)6] b The weight ratio of the structure is 15:100, and in step (1) the reaction temperature is 80°C and the reaction time is 4 hours.
[0137] More specifically, first, 648.82 g of ferric chloride (4 mol) and 329.24 g of potassium hexacyanoferrate (III) (1 mol) were dissolved in deionized water and tert-butyl alcohol aqueous solution (volume ratio 50 / 50), respectively, with a concentration of 20 wt%; then the potassium hexacyanoferrate (III) solution was added dropwise to the ferric chloride, the dropping process could not be too fast, and the stirring was ensured to be uniform; after the dropping was completed, the temperature was raised, and the heating switch was turned off after being kept at 80° C. for 4 hours; 42 g of polyether polyol with a number average molecular weight Mn of 1000 was dropped in sequence (so that the polyether polyol and M` a [M``(CN)6] b The weight ratio of the structure is about 15:100) and 28g pyrophosphoric acid (so that the pyrophosphoric acid and M' a [M``(CN)6] b The weight ratio of the structure is about 10:100), and uniform stirring must be ensured after the addition is completed; finally, the mixture is filtered out after cooling to room temperature, and the product obtained by filtration is washed with tert-butyl alcohol aqueous solution, and the precipitate obtained by centrifugation is freeze-dried for use and named DMC-2.
[0138] The catalytic performance of DMC-2 was tested. The calculation and verification methods of the catalyst structure were the same as those in Example 1. The high-temperature thermal stability coefficient was calculated in the same way as in Example 1. The characterization results obtained were as follows: the outer metal and the complex metal in the three-ligand bimetallic complex catalyst DMC prepared in this embodiment were the same. According to the ICP results and ion chromatography, it was deduced that the ratio of the outer metal to the complex metal was 1.64:1. The high-temperature thermal stability coefficient was 0.5% between 200-250°C. The first ligand accounted for 3% of the catalyst weight, the second ligand PPG accounted for 15% of the catalyst weight, and the third ligand FePO4 accounted for 21% of the catalyst weight. Therefore, the structural formula was Fe[Fe(CN)6]·(t-BuOH) 0.186 (PPG) 0.068 ·[FePO4] 0.640Each mole of the three-ligand bimetallic complex catalyst DMC-2 contains 1 mol of Fe[Fe(CN)6], 0.186 mol of the first ligand t-BuOH, 0.068 mol of the second ligand PPG, the second ligand PPG is a polyether polyol with a number average molecular weight of 1000, and 0.640 mol of the third ligand FePO4. The morphology of the three-ligand bimetallic complex catalyst was observed by scanning electron microscopy. It was observed that the shape of the three-ligand bimetallic complex catalyst was irregular spherical, with different sizes, and the pore size was concentrated in the mesopore and micropore range of less than 20 microns. Under such a morphology, the adsorption amount is large, which helps to improve the catalytic activity; the specific surface area of the three-ligand bimetallic complex catalyst was detected by the Quantachrome automatic gas adsorption system (AUTOSORB-1-C) of the full adsorption instrument, and the specific surface area was determined to be 570m by calculating the N2 adsorption curve using the BET formula. 2 / g.
[0139] Example 3
[0140] The purpose of Example 3 is to test the influence of the acid-base properties of the material. Specifically, alkaline phosphoric acid derivatives are selected to replace the medium-strong acid phosphoric acid and pyrophosphoric acid in Example 1 and Experimental Example 2 to prepare the three-ligand bimetallic complex catalyst DMC. The preparation method is basically the same as that in Example 1.
[0141] More specifically, in the present embodiment, PCEL is selected as a carbon dioxide-based polycarbonate-polyether polyol with a number average molecular weight Mn of 300 to 2000, and Example 3 selects a carbon dioxide-based polycarbonate-polyether polyol with a number average molecular weight Mn of 2000. The purpose is to increase the electronic content of the polyol, enhance the coordination ability, and increase the thermal decomposition temperature of the three-ligand bimetallic complex catalyst DMC. In the selected carbon dioxide-based polycarbonate-polyether polyol, the e value range is 2 to 23, the f value range is 0 to 13, and the e+f value range is 2 to 25. By controlling the number average molecular weight and specific amount of the PCEL fed, the composition structure parameter n of the preparation of the three-ligand bimetallic complex catalyst DMC is controlled to account for 5-20% of the total weight of the catalyst.
[0142] More specifically, in this embodiment, the cyanide metal complex salt is selected from sodium hexacyanocobaltate, also known as sodium cobalt cyanide; the soluble metal salt of the metal ion M' is selected from zinc bromide, the weight concentration of the soluble cyanide metal complex salt and the soluble metal salt are 30wt% respectively, the volume percentage concentration of the tert-butyl alcohol aqueous solution is 60%, and the ratio of the molar number of the soluble cyanide metal complex salt to the molar number of the soluble metal salt is 1:4. The phosphoric acid derivative is selected as potassium phosphate to obtain the third ligand M'(PO4) x It is Zn3(PO4)2.
[0143] More specifically, in this embodiment, first, 900.87g of zinc bromide (4 mol) and 284g of sodium hexacyanocobaltate (1 mol) are dissolved in tert-butyl alcohol-water solution (volume ratio 60 / 40), and the concentration is 30wt%; then the sodium hexacyanocobaltate solution is added dropwise to the zinc bromide, and the dropping process cannot be too fast, and the stirring must be uniform; after the dropping is completed, the temperature is raised, and the heating switch is turned off after being kept at 80°C for 2 hours; 48.68g of carbon dioxide-based polycarbonate-polyether polyol with a number average molecular weight Mn=2000 (so that the carbon dioxide-based polycarbonate-polyether polyol and M' a [M``(CN)6] b The weight ratio of the structure is about 15:100) and 32 grams of potassium phosphate (so that potassium phosphate and M' a [M``(CN)6] b The weight ratio of the structure is about 10:100), and after the addition is completed, it is necessary to ensure uniform stirring; finally, after cooling to room temperature, the material is filtered out, washed with tert-butyl alcohol aqueous solution, centrifuged to obtain a precipitate, and then freeze-dried for use, named DMC-3.
[0144] The catalytic performance of DMC-3 was tested, and the calculation and verification methods of the catalyst structure were the same as those in Example 1. The high-temperature thermal stability coefficient calculation method was the same as that in Example 1. The characterization obtained was that in the three-ligand bimetallic complex catalyst DMC-3 prepared in this embodiment, Zn:Co=1.63:1, the high-temperature thermal stability coefficient was 0.7% between 200-250°C, the first ligand accounted for 8% of the catalyst weight, the second ligand PCEL accounted for 10% of the catalyst weight, and the third ligand Zn3(PO4)2 accounted for 4% of the catalyst weight, so the structural formula was Zn3[Co(CN)6]2·(t-BuOH) 0.9 (PCEL) 0.042 ·[Zn3(PO4)2] 0.089 Each mole of the three-ligand bimetallic complex catalyst DMC-3 contains 1 mol Zn3[Co(CN)6]2, 0.9 mol of the first ligand t-BuOH, 0.042 mol of the second ligand PCEL, the second ligand PCEL is a carbon dioxide-based polycarbonate-polyether polyol with a number average molecular weight of 2000, and 0.089 mol of the third ligand Zn3(PO4)2. The morphology of the three-ligand bimetallic complex catalyst was observed by scanning electron microscopy, and it was observed that the shape of the three-ligand bimetallic complex catalyst was irregular spherical, with different sizes, and the pore size was concentrated in the mesopore and micropore range of less than 20 microns. Under such a morphology, the adsorption amount is large, which helps to improve the catalytic activity; the specific surface area of the three-ligand bimetallic complex catalyst was detected by the Quantachrome automatic gas adsorption system (AUTOSORB-1-C) of the full adsorption instrument, and the specific surface area was determined to be 300m by calculating the N2 adsorption curve using the BET formula.2 / g.
[0145] Example 4
[0146] The purpose of Example 4 is to test the influence of the concentration of the tert-butanol aqueous solution of the material. Specifically, 90% tert-butanol aqueous solution is used to replace the tert-butanol aqueous solution of Example 1, Experimental Example 2, and Experimental Example 3 to prepare the three-ligand bimetallic complex catalyst DMC. The preparation method is basically the same as that of Example 1.
[0147] More specifically, in the present embodiment, PCEL is selected as a carbon dioxide-based polycarbonate-polyether polyol with a number average molecular weight Mn of 1500. By increasing the electron cloud on the polyol, the coordination ability of the macromolecule is improved, and the heat resistance of the three-ligand bimetallic complex catalyst DMC is enhanced. By controlling the number average molecular weight and specific amount of the PCEL fed, the composition structure parameter n of the three-ligand bimetallic complex catalyst DMC is controlled to account for 5-20% of the total weight of the catalyst.
[0148] More specifically, in this embodiment, the cyanide metal complex salt is selected from sodium hexacyanocobaltate; the soluble metal salt of the metal ion M' is selected from nickel chloride, the weight concentration of the soluble cyanide metal complex salt and the soluble metal salt are 10wt% respectively, the volume percentage concentration of the tert-butyl alcohol aqueous solution is 90%, and the ratio of the molar number of the soluble cyanide metal complex salt to the molar number of the soluble metal salt is 1. The phosphoric acid derivative is selected as disodium hydrogen phosphate to obtain the third ligand M'(PO4) x It is Ni3(PO4)2.
[0149] More specifically, in this embodiment, first, 388.797g of nickel chloride (3 mol) and 284g of sodium hexacyanocobaltate (1 mol) are dissolved in deionized water and tert-butyl alcohol aqueous solution (volume ratio 90 / 10), respectively; then the sodium hexacyanocobaltate solution is added dropwise to the nickel chloride, the dropping process cannot be too fast, and the stirring must be uniform; after the dropping is completed, the temperature is raised, and the heating switch is turned off after being kept at 80°C for 3 hours; 31.49g of carbon dioxide-based polycarbonate-polyether polyol with a number average molecular weight Mn=1500 is dropped in turn (so that the carbon dioxide-based polycarbonate-polyether polyol and M' a [M``(CN)6] b The weight ratio of the structure is about 10:100) and 15.75g disodium hydrogen phosphate (disodium hydrogen phosphate and M` a [M``(CN)6] b The weight ratio of the structure is about 5:100) After the addition is completed, ensure that the stirring is uniform; finally, after cooling to room temperature, filter and discharge the material, wash with tert-butyl alcohol-water solution, centrifuge, and then freeze-dry for use, named DMC-4.
[0150] The catalytic performance of DMC-4 was tested, and the calculation and verification methods of the catalyst structure were the same as those in Example 1. The high-temperature thermal stability coefficient calculation method was the same as that in Example 1. The characterization obtained was that the three-ligand bimetallic complex catalyst DMC-4 prepared in this embodiment has Ni:Co=2.54:1, and the high-temperature thermal stability coefficient is 1% between 200-250°C. The first ligand accounts for 3% of the catalyst weight, the second ligand PCEL accounts for 20% of the catalyst weight, and the third ligand Ni3(PO4)2 accounts for 22% of the catalyst weight, so the structural formula is Ni3[Co(CN)6]2·(t-BuOH) 0.46 (PCEL) 0.15 ·[Ni3(PO4)2] 0.69 Each mole of the three-ligand bimetallic complex catalyst DMC-4 contains 1 mol Ni3[Co(CN)6]2, 0.46 mol of the first ligand t-BuOH, 0.15 mol of the second ligand PCEL, the second ligand PCEL is a carbon dioxide-based polycarbonate-polyether polyol with a number average molecular weight of 1500, and 0.69 mol of the third ligand Ni3(PO4)2. The morphology of the three-ligand bimetallic complex catalyst was observed by scanning electron microscopy, and it was observed that the three-ligand bimetallic complex catalyst was irregularly spherical in shape with different sizes, and the pore size was concentrated in the mesopore and micropore range of less than 20 microns. Under such a morphology, the adsorption amount is large, which helps to improve the catalytic activity; the specific surface area of the three-ligand bimetallic complex catalyst was detected by the Quantachrome automatic gas adsorption system (AUTOSORB-1-C) of the full adsorption instrument, and the specific surface area was determined to be 368m by calculating the N2 adsorption curve using the BET formula. 2 / g.
[0151] Example 5
[0152] The purpose of Example 5 is to test the influence of the material complexation reaction conditions. Specifically, the reaction temperature is 70°C and the reaction time is 2 hours. The corresponding experimental conditions in Example 1, Experimental Example 2, Experimental Example 3, and Experimental Example 4 are replaced to prepare the three-ligand bimetallic complex catalyst DMC. The preparation method is basically the same as that in Example 1.
[0153] More specifically, in this embodiment, PCEL is selected as a carbon dioxide-based polycarbonate-polyether polyol (PCEL) with a number average molecular weight Mn of 600. The selected polyol e value ranges from 5 to 7, the f value ranges from 0 to 3, and the e+f value ranges from 3 to 8. By controlling the number average molecular weight and specific amount of the PCEL fed, the composition structure parameter n of the preparation of the tri-ligand bimetallic complex catalyst DMC is controlled, accounting for 5-20% of the total weight of the catalyst.
[0154] More specifically, in this embodiment, the cyanide metal complex salt is potassium hexacyanoiridate (III) hydrate; the soluble metal salt of the metal ion M' is tin chloride, the weight concentration of the soluble cyanide metal complex salt and the soluble metal salt is 30wt%, the volume percentage concentration of the tert-butyl alcohol aqueous solution is 90%, and the ratio of the molar number of the soluble cyanide metal complex salt to the molar number of the soluble metal salt is 1. The phosphoric acid derivative is potassium dihydrogen phosphate, and the third ligand M'(PO4)x is Sn3(PO4)4.
[0155] More specifically, in this embodiment, first, 781.54 g of tin chloride (3 mol) and 483.63 g of potassium hexacyanoiridate (III) hydrate (1 mol) were dissolved in deionized water and tert-butyl alcohol aqueous solution (volume ratio 90 / 10), respectively; then the potassium hexacyanoiridate (III) solution was added dropwise to the tin chloride solution, the dropping process could not be too fast, and uniform stirring was ensured; after the dropping was completed, the temperature was raised, and the heating switch was turned off after being kept at 70° C. for 2 hours; 58.40 g of PCEL with a number average molecular weight of Mn=600 (so that PCEL and M` a [M``(CN)6] b The weight ratio of the structure is about 13:100) and 22.46 grams of potassium dihydrogen phosphate (the purpose is to maintain the pH value in a relatively neutral and slightly acidic environment during the complexation reaction in step (2). Potassium dihydrogen phosphate and M` a [M``(CN)6] b The weight ratio of the structure is about 5:100) After the addition is completed, ensure that the stirring is uniform; finally, after cooling to room temperature, filter and discharge the material, wash with tert-butyl alcohol-water solution, centrifuge, and then freeze-dry for use, named DMC-5.
[0156] The catalytic performance of DMC-5 was tested, and the calculation and verification methods of the catalyst structure were the same as those in Example 1. The high-temperature thermal stability coefficient calculation method was the same as that in Example 1. The characterization obtained was that in the three-ligand bimetallic complex catalyst DMC-5 prepared in this embodiment, Sn:Ir=1.5:1, the high-temperature thermal stability coefficient was 0.3% between 200-250°C, the first ligand accounted for 3% of the catalyst weight, the second ligand PCEL accounted for 15% of the catalyst weight, and the third ligand Sn3(PO4)4 accounted for 10% of the catalyst weight, so the structural formula was Sn3[Ir(CN)6]4·(t-BuOH) 1.25 (PCEL) 0.77·[Sn3(PO4)4], each mole of the three-ligand bimetallic complex catalyst DMC-5 contains 1 mol Sn3[Ir(CN)6]4, 1.25 mol of the first ligand t-BuOH, 0.77 mol of the second ligand PCEL, the second ligand PCEL is a carbon dioxide-based polycarbonate ester-polyether polyol, with a number average molecular weight of 600, and 1 mol of the third ligand Sn3(PO4)4. The morphology of the three-ligand bimetallic complex catalyst was observed by scanning electron microscopy, and it was observed that the shape of the three-ligand bimetallic complex catalyst was irregular spherical, with different sizes, and the pore size was concentrated in the mesopore and micropore range of less than 20 microns. Under such a morphology, the adsorption amount is large, which helps to improve the catalytic activity; the specific surface area of the three-ligand bimetallic complex catalyst was detected by the Quantachrome automatic gas adsorption system (AUTOSORB-1-C) of the full adsorption instrument, and the specific surface area was determined to be 417m by calculating the N2 adsorption curve using the BET formula. 2 / g.
[0157] Comparative Example 1
[0158] Comparative Example 1 chooses to purchase DMC catalyst with a relatively high sales volume on the market. The detailed preparation method of the catalyst can be found in Chinese patent (ZL202010263219.6). It is directly named DMC-CK1. Catalyst DMC-CK1 is used for the ring-opening polymerization reaction of alkylene oxide. The structure of DMC-CK1 is M 1 a [M 2 b (CN) c ] d ·xM 1 (X) e ·jT·wL1·yL2·zL3, the content of each component: Zn=20.5%, Co=10.1%, tert-butanol=1.5%, L1=6.5%, L2=6.5%, L3=9.7%.
[0159] Thermogravimetric comparison of DMC-1 and DMC-CK1 showed that the structure of DMC-CK1 was unstable in an inert atmosphere at high temperature, while DMC-1 was relatively stable. Figure 1 . Calculate the high temperature thermal stability coefficient of the catalyst according to the high temperature thermal stability coefficient L calculation formula:
[0160]
[0161] m% refers to the mass percentage at the temperature corresponding to any point on the thermogravimetric curve, T1 and T2 are the temperatures corresponding to any point on the thermogravimetric curve, and the value ranges of T1 and T2 are 200-250°C, respectively, and T1>T2; preferably, the value ranges of T1 and T2 are 220-250°C, respectively; the high-temperature thermal stability coefficient of the DMC-CK1 catalyst in Comparative Example 1 is 8.6%, so the high-temperature thermal stability of the commercially available catalyst DMC-CK1 is significantly worse than that of the DMC-1 of the present invention.
[0162] Comparative Example 2 refers to the Chinese patent "Continuous Preparation of Double Metal Cyanide Complex Catalyst Process" (Patent No.: ZL02113022.1). The purpose of the comparative example is to prepare a structure of M' a [M``(CN)6] b ·(t-BuOH) m (Poly) n A tetraligand bimetallic complex catalyst DMC of ·A·B, A is a soluble salt, B is an organosiloxane containing a Si-C chain, and the preparation method refers to the above patent. The obtained catalyst is named DMC-CK2, and the high temperature thermal stability coefficient of the DMC-CK2 catalyst in Comparative Example 2 is 5%.
[0163] The tetraligand bimetallic complex catalyst DMC of Comparative Example 2 is mainly different from Examples 1 to 5 of the present invention in that:
[0164] (1) The second ligand of the present invention controls the surface active tension of the ligand by adjusting the hydrocarbon chain lengths of R1 and R2. The corresponding ligand in Comparative Example 1 is an organosiloxane.
[0165] (2) The third ligand M'(PO4) of the present invention x It is poorly soluble in water, and its solubility product is generally greater than 20 at room temperature and neutral pH, while the corresponding ligand in Comparative Example 1 is a sulfate or chloride salt of Zn, Fe, or Ni, which is soluble in water at room temperature and at the polymerization reaction temperature.
[0166] Experimental catalytic reaction example 1
[0167] The purpose of the experimental catalytic reaction example is to use the catalysts DMC-1 to DMC-5 of the present invention and the catalyst DMC-CK1 of comparative example 1 and the catalyst DMC-CK2 of comparative example 2 for polymerization reactions to prepare polyether polyols, and to compare their performance differences at conventional reaction temperatures, that is, when the temperature in the reactor is lower than 200°C during the polymerization reaction.
[0168] Feeding period: 0.1270 g of catalyst (30 ppm, relative to the total mass of propylene oxide and succinic acid) and 93.81 g of succinic acid (molar ratio 90:1) were weighed and added into a dry 10 L high pressure (5 MPa-10 MPa) autoclave, 5 L of propylene oxide was quickly injected, and then the autoclave was sealed. The catalysts were selected from DMC-1 to DMC-5 and the catalyst DMC-CK of Comparative Example 1.
[0169] Reaction period: The autoclave is heated to raise the temperature inside the autoclave to 90°C. During this process, the epoxy compound added to the autoclave begins to activate the catalyst to produce a large number of active centers, inducing the epoxy compound to start polymerization and release a large amount of heat, resulting in high temperature and high pressure in the autoclave. At the same time, the controllability of the reaction deteriorates, which is specifically manifested by a sudden increase in the pressure inside the autoclave. Correspondingly, a rapid drop in the pressure inside the autoclave is a feature of complete activation of the catalyst. Generally, a sudden drop in the pressure inside the autoclave is regarded as the end of the induced activation period. For detailed descriptions, see Chinese Patent (Patent Publication No.: CN1145655C) and Chinese Patent (Patent Publication No.: CN1880359A). Generally, the activation time of the bimetallic complex catalyst DMC is more than 1 hour, see Chinese Patent (Patent Publication No.: CN103534029B). At the end of the induced activation period, the temperature inside the autoclave is generally above 110°C. Without heating, the temperature in the autoclave slowly decreases. When the temperature in the autoclave is close to the set temperature, the temperature of the autoclave is increased to maintain the temperature at 120°C. After about 1 hour, the pressure display reads 0, the polymerization reaction is over, and the heating is stopped. When the temperature is lower than 30°C, which is lower than the boiling point of propylene oxide, the vacuum system is opened to remove the low-boiling propylene oxide, and the conversion rate is calculated.
[0170] Ripening period: Start the vacuum system, turn on the heating system, set to 55°C, turn off the vacuum after 30 minutes, turn off the heating, the purpose of this process is to extract the unreacted propylene oxide (boiling point 34°C) product, open the autoclave after the end, visually observe the product color, place the PID detector at the bottle mouth, after the data is stable. Take out the product, weigh it, calculate the conversion rate, and bottle the product for later use. The product parameters are shown in Table 1.
[0171] Table 1 Parameters of products obtained by polymerization reaction catalyzed by bimetallic complex catalyst DMC at conventional reaction temperature
[0172]
[0173] * 1. Conversion rate % = (m 聚醚多元醇 -m 丁二酸 ) / m PO *100%, where m is the mass of each substance.
[0174] From the results in Table 1, we can see that when the temperature is lower than 200°C, under the same reaction conditions, compared with DMC-CK1 and the catalyst DMC-CK2 of the Chinese patent "Continuous Preparation of Double Metal Cyanide Complex Catalyst" (patent number: ZL02113022.1), the catalyst of the prepared bimetallic DMC of the present invention has a high catalytic conversion rate, that is, a high catalyst activity. The reason is that the three-ligand bimetallic complex catalyst DMC-1 to DMC-5 of the present invention can be quickly activated and have high activity in the same time in the presence of a large amount of initiator succinic acid, i.e., "passivation agent", indicating that DMC-1 to DMC-5 are not sensitive to active hydrogen groups, or have more active groups, which fully meet the reaction requirements. Specifically, the propylene oxide conversion rate is as high as 95%, and a polyether polyol product with a lower VOC level is obtained. The generation of VOC comes from low-polymerization polyether polyols, usually with a polymerization degree of less than 10, and their boiling points are relatively low. The molecular weight polydispersity index is a parameter that characterizes the heterogeneity of polymer molecular weight, and is characterized by the ratio of weight average to number average molecular weight or the ratio of Z average to weight average molecular weight. The polymer molecular weight polydispersity index (PDI) is related to the molecular weight. Generally, the distribution will be narrower when the molecular weight is small, because the molecular weight is small and the movement speed is fast, and the uniformity is high. The molecular weight polydispersity index (PDI) of the polymer molecular weight is large, and the chain segments move slowly, which is easy to cause a wide distribution. However, the molecular weight distribution of high molecular weight polyols is about 2, which does not affect the use.
[0175] Experimental catalytic reaction example 2
[0176] The purpose of Experimental Catalytic Reaction Example 2 is to test the heat resistance performance of the catalyst. The difference from Experimental Catalytic Reaction Example 1 is that the temperature in the kettle is 220°C, so that the peak temperature in the kettle naturally rises to above 250°C to prepare polyether polyols and compare their performance differences at higher reaction temperatures.
[0177] Feeding period: Weigh 0.1317 g of DMC catalyst (30 ppm, relative to the total mass of propylene oxide and succinic acid) and 49.66 g of succinic acid (molar ratio 170:1) and add them into a dry 10 L high pressure (5 MPa-10 MPa) autoclave, quickly inject 5 L of propylene oxide, seal the autoclave, and the pressure reading in the autoclave is zero. The catalysts are DMC-1-DMC-5 and the catalyst DMC-CK of Comparative Example 1.
[0178] Reaction period: Set the starting temperature at 90℃, the pressure in the kettle increases slowly, when the temperature in the kettle rises to 90℃, the pressure increases suddenly and then drops suddenly, at this time the temperature in the kettle also reaches the peak value, the peak value is related to the type and quantity of the mixture in the kettle, under this condition, the peak value is 210-260℃, the temperature slowly drops, and after dropping to 200℃. Give the temperature in the kettle to 220℃, there is no pressure indication after 1h, stop providing heat.
[0179] Ripening period: Start the vacuum system, turn on the heating system, set to 55°C, turn off the vacuum and heating after 30 minutes. The purpose of this process is to extract the unreacted propylene oxide (boiling point 34°C) product. After the end, open the autoclave, visually observe the product color, place the PID detector at the bottle mouth, and after the data is stable, take out the product, weigh it, calculate the conversion rate, and bottle it for later use. The product parameters are shown in Table 2.
[0180] Table 2 Catalytic activity of bimetallic complex catalyst DMC when the reactor temperature is higher than 200℃
[0181]
[0182] From the results in Table 2, we can get that compared with the catalyst of the Chinese patent "Continuous Preparation of Double Metal Cyanide Complex Catalyst Process" (Patent No.: ZL02113022.1), the number average molecular weight of the polyether polyol prepared by the catalytic polymerization of the three-ligand bimetallic complex catalyst DMC prepared in the present invention is significantly higher, and the gap is obvious. This is related to the level of conversion rate. The higher the conversion rate, the greater the molecular weight. In this experimental catalytic reaction example, during the polymerization reaction, the active groups in the autoclave are reduced, resulting in a slowdown in the growth of the molecular weight of the polyether polyol, until there are no active groups in the autoclave, the molecular weight of the polyether polyol will no longer increase. The inventors of the present invention compared the VOC content and color of the polyether polyol products and found that the polyether polyol products catalytically polymerized by DMC-CK1 of Comparative Example 1 and the bimetallic DMC-CK2 of Comparative Example 2 are yellow and have a high VOC content. The boiling point is related to the molecular weight. The larger the molecular weight, the higher the boiling point, and vice versa. The polyether polyol product should be colorless, but it appears yellow in the comparative example application. The reason is that the polyether polyol product is mixed with the catalyst DMC-CK with a destroyed structure and free metal ions, mainly metal cobalt ions (+3 valence) are freed due to the destruction of the catalyst DMC-CK structure, which makes the polyether polyol product show color. As the exposure time in the air increases, it is found that the color of the polyether polyol product obtained by the embodiment and the comparative example is different. The color of the polyether polyol catalyzed by the embodiment is always colorless, while the result of the comparative example catalysis changes from yellow to light pink. This is because the cobalt ions in the exposed catalyst undergo oxidation reaction with oxygen in the air and become +2 valence red.
[0183] Comparing Table 1 and Table 2, it can be seen that DMC-1 to DMC-5 can all exhibit high catalytic activity at conventional temperatures below 200°C or high temperatures (greater than or equal to 200°C), and the product performance is colorless with low VOC content, which means that the obtained DMC catalyst has high temperature resistance and high activity, and is applicable to a wide temperature range, which meets the application requirements in reactions with uncontrollable heat generation (uncontrollable heat generation refers to the spontaneous release or absorption of a large amount of heat during the reaction).
[0184] Comparing Table 1 and Table 2, it is found that when the initiator succinic acid and propylene oxide are added together with the prepared three-ligand bimetallic complex catalyst DMC-1 to DMC-5 of the present invention, the DMC catalyst of the present invention still maintains high-efficiency catalysis, indicating that the catalytic center of the DMC catalyst of the present invention is not easy to deactivate. The role of the initiator is to provide the starting point of the molecular chain. The more starting points, the more molecular chains, and the molecular weight will be correspondingly reduced in the equal amount of products. The initiator provides the position where the free radical starts to polymerize. The inventors of the present invention also found that the DMC catalyst of the present invention should show a passivation phenomenon when the initiator exists. Unexpectedly, the initiator passivates the DMC catalyst of the present invention and plays an important positive role. The initiator passivates the DMC catalyst of the present invention and unexpectedly regularizes the disordered polyether polyol molecular chain, which can adjust the molecular weight of the polyether polyol and reduce the dispersibility index of the polymer. In Table 1 and Table 2, the molecular weights of the polyether polyols prepared by the prepared three-ligand bimetallic complex catalysts DMC-1 to DMC-5 of the present invention are different. One reason is that the number of initiators is different. By comparison, it can be seen that the amount of initiator in Table 2 is less, almost half of that in Table 1, and the molecular weight is nearly doubled. From the data in Tables 1 and 2, it can also be seen that when the DMC catalyst of the present invention is used in the reaction of equal amounts of epoxy compounds and with similar conversion rates, the molecular weight of the product polyether polyol is inversely proportional to the molar concentration of the initiator, which has guiding significance for using the DMC catalyst of the present invention to produce polyether polyols of other molecular weights.
[0185] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some of the technical features can be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A three-ligand bimetallic complex catalyst, characterized in that: The structure of the three-ligand bimetallic complex catalyst is Ma`a[M``(CN)6]b·(t-BuOH)m·(Poly)n·[M`c(PO4)d]y, wherein: The first ligand t-BuOH is tert-butyl alcohol, The second ligand Poly is selected from polyether polyols or their derivatives with a number average molecular weight Mn of 300 to 2000, The third ligand is phosphate, The general structural formula of the polyether polyol is represented by formula (I): In formula (I), the value of e ranges from 0 to 40, the value of f ranges from 0 to 40, the value of e+f ranges from 2 to 45, and R1 to R2 are independently hydrogen atoms or monovalent hydrocarbon groups having 1 to 5 carbon atoms; The atomic molar ratio of M` to M`` is 1.5 to 3:1, M` is selected from Zn 2+ , Fe 3+ 、Ni 2+ Sn 4+ , Pb 2+ ,M`` is selected from Co 3+ , Fe 3+ , Ir 3+ , a, b, c, d are ionic coefficients, satisfying the balance of positive and negative charges, m, n, y are any positive numbers, The weight proportions of the ligands are: The weight of the first ligand t-BuOH is 0.05 to 10% of the total weight of the three-ligand bimetallic complex catalyst; The weight of the second ligand Poly is 5 to 20% of the total weight of the tri-ligand bimetallic complex catalyst; The weight of the third ligand phosphate is 4 to 30% of the total weight of the three-ligand bimetallic complex catalyst; The derivative of the polyether polyol is a carbon dioxide-based polycarbonate-polyether polyol, and its general structural formula is represented by formula (II): In formula (II), the value of e ranges from 2 to 23, the value of f ranges from 0 to 13, the value of e+f ranges from 2 to 25, and the number average molecular weight Mn of the second ligand Poly is 300 to 2000; The preparation method of the three-ligand bimetallic complex catalyst comprises the following steps: (1) weighing a soluble metal salt of metal ion Mˋ, a soluble metal cyanide complex salt of metal ion Mˋˋ, dissolving the soluble metal cyanide complex salt of metal ion Mˋˋ in deionized water, and dissolving the soluble metal salt of metal ion Mˋˋ in a tert-butyl alcohol-water solution, and then adding the materials into a reaction device, stirring evenly to obtain a metal cyanide complex solution system, and then under the conditions of a reaction temperature of 70 to 90° C. and a reaction time of 2 to 6 hours, a complex reaction occurs in the metal cyanide complex solution system to form a Mˋa[Mˋˋ(CN)6]b·(t-BuOH)m structure; Wherein, the metal ion M is selected from Zn 2+ , Fe 3+ 、Ni 2+ Sn 4+ , Pb 2+ , the metal ion Mˋˋ is selected from Co 3+ , Fe 3+ , Ir 3+ , The ratio of the molar number of the soluble metal cyanide complex salt to the molar number of the soluble metal salt is 1:2-5. The volume ratio concentration of the tert-butyl alcohol-water solution is 40-98%, and the weight concentrations of the soluble cyanide metal complex salt and the soluble metal salt in the cyanide metal complex solution system are 10%-40wt% respectively; (2) After step (1) is completed, heating is stopped, and Poly, phosphoric acid or its derivatives are added to the reaction device, and the residual heat of the reaction in step (1) is used to react, and when the temperature drops to room temperature, Mˋ a [Mˋˋ(CN)6] b ·(t-BuOH) m (Poly) n ·[Mˋ c (PO4) d ] y Ligand structure; the phosphoric acid derivative is selected from any one of potassium hydrogen phosphate, sodium hydrogen phosphate, potassium dihydrogen phosphate, sodium dihydrogen phosphate, sodium pyrophosphate, acidic sodium pyrophosphate, and metaphosphoric acid; (3) After step (2), the material is filtered and then washed with a tert-butyl alcohol-water solution to remove unreacted metal ions and uncoordinated Poly and phosphoric acid or its derivatives, and then vacuum dried to obtain a tripartite bimetallic complex catalyst.
2. The three-ligand bimetallic complex catalyst according to claim 1, characterized in that: The atomic molar ratio of Mˋ to Mˋˋ is 1.65~2.54:
1.
3. The three-ligand bimetallic complex catalyst according to claim 1, characterized in that: The weight of the first ligand t-BuOH is 3-8% of the total weight of the three-ligand bimetallic complex catalyst; the weight of the second ligand Poly is 8-15% of the total weight of the three-ligand bimetallic complex catalyst; the weight of the third ligand phosphate is 4-25% of the total weight of the three-ligand bimetallic complex catalyst.
4. The three-ligand bimetallic complex catalyst according to claim 1, characterized in that: The tri-ligand bimetallic complex catalyst is structurally stable at 200-250° C. in an inert atmosphere, and the high-temperature thermal stability coefficient L is ≤1.2%. The inert atmosphere refers to a gas that does not have an oxidizing property. The high-temperature thermal stability coefficient L is calculated as follows: m% refers to the residual mass percentage at the temperature corresponding to any point on the thermogravimetric curve, T1 and T2 are the temperatures corresponding to any point on the thermogravimetric curve, and the value ranges of T1 and T2 are 200-250°C, respectively, and T1>T2.
5. The three-ligand bimetallic complex catalyst according to claim 4, characterized in that: The value ranges of T1 and T2 are 220~250℃ respectively.
6. The three-ligand bimetallic complex catalyst according to claim 1, characterized in that: The tri-ligand bimetallic complex catalyst has a stable structure at 220-250° C. in an inert atmosphere.
7. The three-ligand bimetallic complex catalyst according to claim 1, characterized in that: The three-ligand bimetallic complex catalyst is in the shape of an irregular sphere.
8. The three-ligand bimetallic complex catalyst according to claim 1, characterized in that: The specific surface area of the three-ligand bimetallic complex catalyst is 300 to 570 m 2 / g.
9. The three-ligand bimetallic complex catalyst according to claim 1, characterized in that: The soluble cyanide metal complex salt of the metal ion M`` is selected from potassium hexacyanocobaltate, sodium hexacyanocobaltate, potassium hexacyanoferrate (III) or zinc hexacyanoiridate (III), And / or the soluble metal salt of the metal ion M' is selected from one of zinc chloride, zinc bromide, ferric chloride, nickel chloride, tin chloride and lead chloride.
10. The three-ligand bimetallic complex catalyst according to claim 1, characterized in that: The soluble metal cyanide complex salt of the metal ion M`` is potassium hexacyanocobaltate, And / or the soluble metal salt of the metal ion M' is zinc chloride.
11. The three-ligand bimetallic complex catalyst according to claim 1, characterized in that: In step (1), the ratio of the molar number of the soluble metal cyanide complex salt to the molar number of the soluble metal salt is 1:2-4; The volume ratio concentration of the tert-butyl alcohol-water solution is 50 to 90%; The weight concentrations of the soluble metal cyanide complex salt and the soluble metal salt are 15% to 25wt% respectively; The reaction temperature is 80-85°C and the reaction time is 3-5 hours; In step (2), the weight ratio of the charged Poly to the Mˋa[Mˋˋ(CN)6]b structure is 5-20:
100. In step (2), the weight ratio of the phosphoric acid or its derivative added to the Mˋa[Mˋˋ(CN)6]b structure is 5-20:
100.
12. The three-ligand bimetallic complex catalyst according to claim 1, characterized in that: In step (2), the weight ratio of the charged Poly to the Mˋa[Mˋˋ(CN)6]b structure is 10-15:
100. And / or the weight ratio of the phosphoric acid or its derivative added in step (2) to the Mˋa[Mˋˋ(CN)6]b structure is 5-10:
100.
13. The three-ligand bimetallic complex catalyst according to claim 1, characterized in that: In step (3), the volume ratio concentration of the tert-butyl alcohol-water solution is 50-90%; the vacuum drying method is vacuum high temperature drying or vacuum freeze drying.
14. The three-ligand bimetallic complex catalyst according to claim 1, characterized in that: The vacuum drying method is vacuum freeze drying.
15. Use of the tri-ligand bimetallic complex catalyst according to any one of claims 1 to 14 in a chemical reaction.
16. The use according to claim 15, characterized in that The chemical reaction is a polymerization reaction, and the polymerization reaction is a reaction in which an epoxy compound participates.
17. The use according to claim 16, characterized in that The chemical reaction is a reaction in which epoxy compounds participate in the preparation of polyether polyols.
Citation Information
Patent Citations
Alkoxylation products and process for preparing them by means of dmc catalysts
CN102786678A
Method for shortening induction time during catalysis of ring opening polymerization of epoxide in discontinuous method
CN103360595A
Preparation method of high activity double metal cyanide catalyst and its use in the synthesis of polyether polyol
CN103534029B
Method for preparing polyether polyol in recycling manner by aid of DMC (double metal cyanide) catalyst
CN107200837A
A bimetallic cyanide complex catalyst and its preparation method
CN111303401B